2000
DOI: 10.1002/(sici)1097-4636(2000)53:1<111::aid-jbm15>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of retrieved CoCrMo alloy femoral components from PCA artificial total knee joints

Abstract: In this study, we analyzed the surface roughness of retrieved cobalt-chromium-molybdenum (CoCrMo) femoral components of porous coated anatomic (PCA) artificial total knee joints, using a white light interference surface profilometer (WLISP). Thirty-eight PCA retrieved specimens obtained from the Anderson Clinic (Arlington, VA) were used. The artificial knees were originally implanted between 1982-1993, and the specimens were retrieved during revision surgeries between 1988-1996. We examined specimens damaged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Due to these aspects the promotion of full fluid film lubrication and therefore a wear reduction should not be expected in PE articulations. Clinically, metallic wear in metal-PE articulations has been attributed to third bodies such as bone cement or bone particles [14]. However, in this simulator study these types of third bodies were not present.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Due to these aspects the promotion of full fluid film lubrication and therefore a wear reduction should not be expected in PE articulations. Clinically, metallic wear in metal-PE articulations has been attributed to third bodies such as bone cement or bone particles [14]. However, in this simulator study these types of third bodies were not present.…”
Section: Discussionmentioning
confidence: 59%
“…Total knee arthroplasty implants present large metal surface areas, which could lead to metal ion release due to corrosion processes. Furthermore, explanted femoral components show abrasive wear in the form of scratches on the metallic surfaces [14]. It must therefore be expected that TKA leads to an increasing release of metal wear products.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies showed that CoCr retrievals were an order of magnitude rougher than pristine controls [25]. This roughening might explain why UHMWPE inserts paired with CoCr exhibit more surface damage than those paired with OxZr [12] and produce less UHMWPE wear in in vitro studies [4,15,27].…”
Section: Discussionmentioning
confidence: 84%
“…Sixty measurements (four rows of 15 points, each point covering 600 9 800 lm of the component's bearing surface) were taken per condyle, approximately at the location of contact during 308 of flexion (Fig. 2) as suggested by Que et al [24,25]. One pristine, unimplanted OxZr and one pristine CoCr component were measured to provide an estimate of the initial roughness before implantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation